The scattered flock : part five of The marshes of Mount Liang, a new translation of the Shuihu zhuan or Water margin of Shi Nai'an and Luo Guanzhong - Shi, Nai'an, approximately 1290-approximately 1365 (The Chinese University of Hong Kong Press, 2002)
The Scattered Flock, the last volume of this series of translations, contains chapters 91-120 that mark the disastrous end of the 108 heroes. The action in this volume can be divided into three parts: the campaign against Tian Hu, the campaign against Wang Qing and the campaign against Fang La. It is in the last of these that the heroes of Mount Liang begin to die. Their demise is as haphazard and casual as the scattering of the flock of geese when the Prodigy shoots them for mere amusement. But the theme of the vanity of human wishes, the emptiness of ambition, becomes prominent earlier.